Higher EBV response is associated with more severe gray matter and lesion pathology in relapsing multiple sclerosis patients: A case-controlled magnetization transfer ratio study. (March 2020) - Jakimovski, Dejan; Ramanathan, Murali; Weinstock-Guttman, Bianca; Bergsland, Niels; Ramasamay, Deepa P; Carl, Ellen; Dwyer, Michael G; Zivadinov, Robert
Background: Epstein–Barr virus (EBV) infection has been associated with higher clinical activity and risk of multiple sclerosis (MS). Objective: To evaluate associations between EBV-specific humoral response and magnetization transfer ratio (MTR)-derived measure in MS patients and healthy controls (HCs). Methods: The study included 101 MS patients (69 relapsing-remitting multiple sclerosis (RRMS) and 32 secondary-progressive multiple sclerosis (SPMS)) and 41 HCs who underwent clinical, serological, and magnetic resonance imaging (MRI) investigations. MTR values of T1 or T2 lesion volume (LV), normal-appearing (NA) brain tissue (NABT), gray matter (NAGM), and white matter (NAWM) were obtained. Enzyme-linked immunosorbent assay was used to quantify EBV antibody levels. Partial correlations corrected for MRI strength were used, and Benjamini–Hochberg–adjusted p -values < 0.05 were considered significant. Results: MS patients had significantly higher anti-EBV nuclear antigen-1 (EBNA-1) titer when compared to HCs (107.9 U/mL vs 27.8 U/mL, p < 0.001). Within the MS group, higher serum anti-EBNA-1 titer was significantly correlated with lower T1-LV MTR ( r = –0.287, p = 0.035). Within the RRMS group, higher serum anti-EBNA-1 titer was associated with T1-LV MTR ( r = –0.524, p = 0.001) and NAGM MTR ( r = –0.308, p = 0.043). These associations were not present in HCs or SPMS patients. Conclusion: Greater EBV humoral response is associated with lower GM MTR changes and focal destructive lesion pathology in RRMS patients.